Gambaran Kejadian Obesitas pada Karyawan di PT. Putra Perkasa Abadi Site PT. SKS Tumbang Kajuei-Kabupaten Gunung Mas-Kalimantan Tengah - Apir Apir; Defilia Anogra Riani (Inovasi Kesehatan Global, 2024)
Obesity is an excessive accumulation of fat due to an imbalance between energy intake and energy used for a long time and is closely related to the incidence of non-communicable diseases and causes death in 2.8 million adults every year. Based on data from the Indonesian Health Survey, the 2023 national prevalence of obesity in people aged >18 years increased from 21.8% in 2018 to 23.4% in 2024. This research aims to determine the picture of the prevalence of obesity among employees at PT. Putra Perkasa Abadi Site PT. SKS Tumbang Kajuei-Gunung Mas Regency, Central Kalimantan. This research method is a cross-sectional study using secondary data from 2024 from 338 working employees. The results of the research showed that the incidence of obesity was found in respondents with 5% underweight, 29.9% normal, 18.9% at risk, 37% level 1 obesity and 9.2% level 2 obesity.